2021
DOI: 10.3389/fneur.2021.745770
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Reactivity in the Aging Mouse Brain Assessed by Laser Speckle Contrast Imaging and 2-Photon Microscopy: Quantification by an Investigator-Independent Analysis Tool

Abstract: The brain has a high energy demand but little to no energy stores. Therefore, proper brain function relies on the delivery of glucose and oxygen by the cerebral vasculature. The regulation of cerebral blood flow (CBF) occurs at the level of the cerebral capillaries and is driven by a fast and efficient crosstalk between neurons and vessels, a process termed neurovascular coupling (NVC). Experimentally NVC is mainly triggered by sensory stimulation and assessed by measuring either CBF by laser Doppler fluxmetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…Consistent with the small effect of exercise on cerebral microcirculation and oxygenation in superficial cortical areas, we observed no change in the relative peak amplitude or the latency of stimulus-induced hemodynamic response with exercise, assessed with OISI at 570 nm, which emphasizes the intrinsic signal originating from cerebral blood volume changes in the superficial cortical layers ( Figure 3 and Figure 3—figure supplement 1 ; Malonek et al, 1997 ; Tian et al, 2011 ). Young sedentary mice (7 months old) showed a significantly larger relative response amplitude than aged mice, consistent with the reduced cerebrovascular reactivity with age in healthy adults and rodents ( Bálint et al, 2019 ; Barnes, 2015 ; Cai et al, 2023 ; Jessen et al, 2017 ; Seker et al, 2021 ). The baseline CBF can have a strong effect on the magnitude of the hemodynamic response ( Buxton et al, 2004 ; Corfield et al, 2001 ).…”
Section: Discussionsupporting
confidence: 71%
“…Consistent with the small effect of exercise on cerebral microcirculation and oxygenation in superficial cortical areas, we observed no change in the relative peak amplitude or the latency of stimulus-induced hemodynamic response with exercise, assessed with OISI at 570 nm, which emphasizes the intrinsic signal originating from cerebral blood volume changes in the superficial cortical layers ( Figure 3 and Figure 3—figure supplement 1 ; Malonek et al, 1997 ; Tian et al, 2011 ). Young sedentary mice (7 months old) showed a significantly larger relative response amplitude than aged mice, consistent with the reduced cerebrovascular reactivity with age in healthy adults and rodents ( Bálint et al, 2019 ; Barnes, 2015 ; Cai et al, 2023 ; Jessen et al, 2017 ; Seker et al, 2021 ). The baseline CBF can have a strong effect on the magnitude of the hemodynamic response ( Buxton et al, 2004 ; Corfield et al, 2001 ).…”
Section: Discussionsupporting
confidence: 71%
“…(Malonek et al, 1997; Tian et al, 2011) Young sedentary mice (7 months old) showed a significantly larger relative response amplitude than aged mice, consistent with the reduced cerebrovascular reactivity with age in healthy adults and rodents. (Bálint et al, 2019; J. N. Barnes, 2015; Seker et al, 2021) The baseline CBF can have a strong effect on the magnitude of the hemodynamic response. (Buxton et al, 2004; Corfield et al, 2001) While no statistically significant difference in the mean capillary RBC flux in the gray matter was found between the aged sedentary and exercise group (Figure 3b), the exercise group had larger capillary density in the gray matter (Figure 6b), suggesting that cortical blood perfusion was possibly also higher in the exercise group.…”
Section: Discussionmentioning
confidence: 99%
“…For functional activation, constriction and dilation of brain capillaries have been consistently observed in in vivo optical imaging studies. 10,[38][39][40][41][42][43] However, some studies have reported no detectable changes in capillary diameters. 44,45 There could be many reasons for these discrepancies because of the heterogeneous nature and small changes in the capillary diameter responses to functional activations.…”
Section: Discussionmentioning
confidence: 99%